The Role of Attachment Style and Gender of the Trainee Psychotherapist in the Supervisory Relationship/MSc Integrative Counselling and Psychotherapy: Individual Research Project - Feridou Chrysoula (2019)
Abstract, Introduction, Literature Review, Supervision, Supervisory Working Alliance, Attachment, Gender, Gap of the Literature, Methodology, Variables and Design, Participant Details, Materials, Revised Adult Attachment Scale, Supervisory Relationship Questionnaire, Procedure, Ethical Consideration, Results, Discussion, Mail Findings, Additional Findings, Strengths and Limitations, Counseling Implications, Future Research, Conclusion, References, Appendices.